2019
DOI: 10.1038/s41418-019-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

UBAP2L arginine methylation by PRMT1 modulates stress granule assembly

Abstract: Stress granules (SGs) are discrete assemblies of stalled messenger ribonucleoprotein complexes (mRNPs) that form when eukaryotic cells encounter environmental stress. RNA-binding proteins (RBPs) mediate their condensation by recruiting populations of mRNPs. However, the cellular and molecular mechanisms underlying the role of ubiquitin-associated protein 2-like (UBAP2L) in the regulation of SG dynamics remain elusive. Here, we show that UBAP2L is required for both SG assembly and disassembly. UBAP2L overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(135 citation statements)
references
References 49 publications
(65 reference statements)
13
93
0
Order By: Relevance
“…S2A, B). These results show that UBAP2L is a general component of stress granules, consistent with recent data (Huang et al, 2019).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…S2A, B). These results show that UBAP2L is a general component of stress granules, consistent with recent data (Huang et al, 2019).…”
Section: Resultssupporting
confidence: 93%
“…These results show that UBAP2L is a general component of stress granules and it is not only required for arsenite-induced stress granule assembly (Markmiller et al, 2018; Youn et al, 2018) but also for stress granules assembly in other stress conditions, consistent with recent data (Huang et al, 2019). It is interesting that UBAP2L is required for stress granule assembly in heat-shock conditions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, a report indicated that UBAP2L modulates stress granule (SG) assembly (21). SGs are non-membranous cytoplasmic foci composed of non-translating messenger ribonucleoproteins (22).…”
Section: Discussionmentioning
confidence: 99%